ESTUDIO TAXONOMICO EN RHAGOLETIS TOMATIS FOOTE (DIPTERA: TEPHRITIDAE) - Frías L., Daniel; Martínez, Humberto (Acta Entomológica Chilena, 2022)
Rhagoletis tomatis Foote is a Chilean and Peruvian species of Tephritid fly which attacks fruits of Lycopersicum esculentum or tomate. This paper disccuses some taxonomic aspects of both immature stages and adult flies. The results are important to differentiate R. tomatis from congeneric species.